On the stoppage rule in solution for monotone ill-posed problems - Bường, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
The purpose of this note is to present an  iteractive method for solving a regularized equation for nonlinear monotone ill-posed problems in Banach space and  to  study its stoppage rule so that iteractive sequence converges to  a solution of initial problem,  as the noisy data of the right-hand side converges to its exact.